Strategy Adoption and the Performance of Small Scale Rice Processors: Empirical Assessment of Kogi State - Sule, Garba Ja’afaru; Nafiu, Akeem Tunde (Journal of Asian Business Strategy, 2019)
This study focused on the effects of strategy adoption on the performance of small scale rice processors in Kogi State, Nigeria. The study adopted research survey design. The population of the study comprised of 1200 rice processors, from which the sample size of 291 was determined. The study adopted the multi-stage sampling technique to select small scale rice processors in the study area. Data obtained were analyzed using descriptive statistics and Multiple Regression Model. Findings showed that low cost, growth, value and differentiation rice business strategies have significant effects on competitive advantage of small scale rice processors in Kogi State. The study concluded that the choice of strategy to adopt must not be based on intuition, but rather on technical ground and analysis; and that the adoption of combined rice business strategies will depend on adequate level of resources, strategic orientation, knowledge and skills of the small scale rice processors in Kogi State. The study therefore recommended that low costs and differentiation rice business strategies should be combined to achieve increased competitive advantage of small scale rice processors in Kogi State.